Enhancing Transitions of Care: A Cross-Sectional Observational Study on the Role of Clinical Pharmacists in Transition Management in a Latin American Hospital - Zavaleta Monestel, Esteban (2024)
Background The seamless management of transitions of care (TOC) is necessary for patient safety, as it directly correlates with a heightened risk of medication errors and adverse effects. Clinical pharmacists emerge as key stakeholders in optimizing medication management during TOC, specifically during hospital admission and discharge, through the implementation of innovative programs that contribute significantly to the mitigation of medication errors and improve patient satisfaction. Aim This study aims to assess the benefits of pharmacist-led interventions in a Costa Rican private hospital's TOC program for polymedicated and high-risk patients during admission and discharge by identifying and addressing medication errors. Methods A cross-sectional observational study was conducted at Clínica Biblica Hospital in San José, Costa Rica, from February 2022 to May 2023 and focused on polymedicated patients with chronic therapy and high-risk medications. The TOC Medication Program was specifically implemented to focus on medication reconciliation during the admission and discharge processes. A clinical pharmacist documented interventions based on discrepancies found within each patient’s medication and assessed the economic impact of interventions on healthcare personnel during discharge by projecting potential complications in the absence of such interventions, a process that was validated by an internist physician. Results During the medication reconciliation at admission, medication discrepancies, mostly intentional omissions, were successfully addressed by clinical pharmacist interventions with a 90.2% acceptance rate during the admission process. At discharge, 18.9% of medications were high-risk, and nearly 40% of discharges were linked to drug-related problems (DRPs), prompting pharmaceutical interventions. The economic analysis indicated potential savings of $21,010.20 during discharge, demonstrating the substantial impact of interventions in preventing emergency service visits, specialist consults, and hospital admissions. Conclusion Pharmacist-led TOC programs offer important clinical advantages by effectively preventing and rectifying medication discrepancies. These discrepancies, if left unaddressed, pose a potential threat to patient safety. Moreover, the implementation of such programs demonstrates promising economic benefits.